Institutional Barriers to Financing Technology-based Small Firms through Venture Capital Mechanism: A Study to Explore the Incentives for Investment in Iran - Mahmood, Motavaseli; Saeed, Shojaei; Ali, Bitaab; Chitsazan, Hasti; Hasti, Chitsazan; Elyasi, Ghanbar Mohammadi (International Journal of Economics and Financial Issues, 2018)
There is a consensus among scholars that access to financial sources is vital for Technology-Based Small Firms (TBSFs). Venture Capital (VC) financing is the most appropriate external financial source for them. However, VC industry is underdeveloped in most developing countries, e.g. Iran. This paper seeks to discover the causes for “lack of incentives for VC investment” based on institutional theory. In this regard, institutional obstacles constraining the incentives for VC investment in Iran were investigated through conducting 31 detailed interviews. The results suggest that the institutional set-up in Iran motivates the investment in tangible assets, short term projects, large investment schemes and intransparent project rather than TBSFs. Many institutional factors were identified which decrease the incentives for VC investment as: Information disclosure institutions, tax regulations, labor regulations, fiscal institutions, political institutions, commerce and competition regulation, property rights and financial market regulation. Finally, results are discussed and concluded in table 3. Keywords: Venture Capital, Technology-Based Small Firm, Incentives for investment. JEL Classifications: G24; G28; G31; G38; O31